Pengaruh Profitabilitas dan Leverage Terhadap Pengungkapan Emisi Karbon Pada Perusahaan Sektor Industrial Yang Terdaftar Di BEI Dari Tahun 2020 - 2022 - Heru Amrasyid; Irda Rosita; Lisa Amelia Herman (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The purpose of this study is to determine the effect of profitability and leverage on carbon emissions in industrial sector companies listed on the Indonesia Stock Exchange from 2020 - 2022. This type of research uses a quantitative approach in data collection and analysis. The type of data used in this study is quantitative data, which means that the data is obtained in the form of numbers. The source of quantitative data in this study comes from the financial statements of industrial sector companies listed on the Indonesia Stock Exchange in 2020 - 2022. The sample selection in this study used a purposive sampling technique. Data analysis used IBM SPSS software version 25. The results of the study showed that profitability had no effect on the distribution of carbon emissions, leverage had an effect on the distribution of carbon emissions. Together, profitability and leverage had no effect on carbon emissions.